REFORMASI: POLITIK ISLAM DI ERA REFORMASI DI INDONESIA - Supandi Supandi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2019)
Pangangan reform has brought many impacts and changes from the education system that are centralized to decentralized, each of which will have far-reaching consequences in the administration of national education. In general, there are several aspects of the political impact of reform on Islamic education, including 1) Law No. 20/2003 also states that Islamic Boarding Schools, Ma'had Ali, Roudlotul Atfal and majlis taklim are also included in the National education system. 2) The birth of a policy of increasing the budget by 20% from the state budget and regional budget, 3) There is a government policy that requires madrasa as a public school characterized by religion, 4) The existence of Islamic education in Indonesia from the Reformation era until now faces various kinds of problems including : 1) The use of classical Islamic thought, 2) The existence of a conceptual crisis or the limitations of knowledge within the Islamic education system itself, 3) The institutional crisis is caused by a dichotomy between educational institutions that emphasizes one aspect of the existing sciences, whether religious sciences or general sciences.